RELASI PEMBERDAYAAN DAN PARTISIPASI MASYARAKAT DENGAN KERUSAKAN LINGKUNGAN - Hamzah Lubis (Jurnal Kesehatan Masyarakat dan Lingkungan Hidup, 2016)
Entrepreneurs engaged in the management of natural resources have a social responsibility to the local environment. Active role of entrepreneurs to empower the local environment and community impacts positively on the communities and the sustainability of the company itself. This entrepreneur role relation research is conducted in Poncan Marine Resort, Sibolga. The research method is through observation, questionnaires and interviews involving relevant institution at the city scope, employees and tourists. The results shows that the role of entrepreneurs in economic empowerment (10.30%), social (9.0%) and culture (41.40%) is categorized â€œlowâ€. As a result, the capacity of the public (71%) and participation (15.90%) is also low. One of the consequences is dominant reef damages is caused by the public (90%). The coral reefs cover remains ranged from 27.83% to 29% with coral species from 15 to 16 types.Keywords: Corporate roles, Community empowerment, Community capacity, Environmental damage.